Randomized control trial of a decision aid for women considering elective egg freezing: The Eggsurance study protocol. (November 2022) - Peate, Michelle; Sandhu, Sherine; Braat, Sabine; Hart, Roger; Norman, Robert; Parle, Anna; Lew, Raelia; Hickey, Martha
Background: Uptake of elective egg freezing has increased globally. The decision to freeze eggs is complex, and detailed, unbiased information is needed. To address this, we developed an online Decision Aid for women considering elective egg freezing. Decision Aids are the standard of care to support complex health decisions. Objectives: This study will measure the impact of the Decision Aid on decision-making (e.g. decisional conflict, engagement in decision-making, distress, and decision delay) and decision quality (e.g. knowledge, level of informed choice, and regret). Methods and Analysis: A single-blinded two-arm parallel-group randomized controlled trial. Women considering elective egg freezing will be recruited using social media, newsletters, and fertility clinics. Data will be collected at baseline (recruitment), 6-month, and 12-month post-randomization. The primary hypothesis is that the intervention (Decision Aid plus Victorian Assisted Reproductive Technology Authority website) will reduce decisional conflict (measured using the Decisional Conflict Scale) at 12 months more than control (Victorian Assisted Reproductive Technology Authority website only). Secondary outcomes include engagement in decision-making (Perceived Involvement in Care Scale), distress (Depression, Anxiety, and Stress Scale), decision delay, knowledge, informed choice (Multi-dimensional Measure of Informed Choice), and decisional regret (Decisional Regret Scale). Ethics: The study was approved by the University of Melbourne Human Research Ethics Committee (Ethics ID: 2056457). Informed consent will be obtained from all participants prior to enrolment. Discussion: This is the first international randomized controlled trial that aims to investigate the effect of an elective egg freezing Decision Aid on decision-related outcomes (e.g. decisional conflict, informed choice, and regret). It is anticipated that participants who receive the Decision Aid will have better decision and health outcomes. Registration details: ACTRN12620001032943: Comparing different information resources on the process and quality of decision-making in women considering elective egg freezing.